Management of Peutz-Jeghers Syndrome in Children and Adolescents: A Position Paper From the ESPGHAN Polyposis Working Group. Issue 3 (March 2019) - Latchford, Andrew; Cohen, Shlomi; Auth, Marcus; Scaillon, Michele; Viala, Jerome; Daniels, Richard; Talbotec, Cecile; Attard, Thomas; Durno, Carol; Hyer, Warren
Abstract : ABSTRACT: Peutz-Jeghers syndrome (PJS) is a well-described inherited syndrome, characterized by the development of gastrointestinal polyps, and characteristic mucocutaneous freckling. Development of small bowel intestinal polyps may lead to intussusception in children may require emergency laparotomy with potential loss of bowel. Gastrointestinal polyps may lead to bleeding and anemia. This European Society for Paediatric Gastroenterology Hepatology and Nutrition position paper provides a guide for diagnosis, assessment, and management of PJS in children and adolescents and guidance on avoiding complications from PJS or from the endoscopic procedures performed on these patients. This is the first position paper regarding PJS published by European Society for Paediatric Gastroenterology Hepatology and Nutrition. Literature from PubMed, Medline, and Embase was reviewed and in the absence of evidence, recommendations reflect the opinion of pediatric and adult experts involved in the care of polyposis syndromes. Because many of the studies that form the basis for the recommendations were descriptive and/or retrospective in nature, some of the recommendations are based on expert opinion. This position paper will be helpful in the appropriate management and timing of procedures in children and adolescents with PJS.